Effects of silicon treatments on Nilaparvata lugens and rice yield under field conditions (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
The brown planthopper, Nilaparvata lugens (Stål), is a destructive pest of rice crops. In the present work, experiments were conducted to study the impact of an ideal Si rate of 200 kg/ha applied at different splits on brown planthopper infestation and rice yield components under natural field conditions. Results showed that application at a two-equal split of 100 kg Si/ha at 7 and 45 days after transplanting (DAT) significantly controlled the brown planthopper infestation by an average of 59.2% compared to control. However, the fertilisation time did not contribute to giving maximum rice grain yield. The maximum rice grain yield was achieved with 200 kg Si/ha applied once at 25 days after transplanting. The agronomic efficiency of these two methods were 3.79 kg/ha and 4.25 kg/ha, respectively. This may help to explain why a single application of Si during the maximum tillering-reproductive stages (25 DAT) is critical for producing rice grain yield. The application of Si effectively increased the uptake of N, P, and K in rice plants. An increase in these macronutrients in rice plants may be the reason why rice plants effectively hindered the brown planthopper infestation and also provided greater nutrients for sustaining the rice grain yield. Overall, the application during the early vegetative (7 DAT) and reproductive (45 DAT) stages sheds light on how Si application influences the rice plants' defence mechanisms against brown planthoppers but sacrifices the grain yield. Future research on silicon applications and integration with biological control for ecologically sustainable pest management in rice should be considered.
Keywords: brown planthopper; fertiliser; grain yield; agronomic efficiency; rice pest